(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2011)
The aim of this study is to investigate the anti-inflammatory effects of simvastatin alone and in combination with aspirin, the most widely used analgesic, antipyretic and anti-inflammatory agent, and to evaluate the effect of using them in combination which may produce synergistic effect and lower the dose required for each agent. 72 Male Wistar albino rats suffering from air pouch granuloma were used. They were divided into 12 groups each comprising 6 rats, they received either simvastatin (20 mg/kg/day) or aspirin (25 mg/kg/day) or combined therapy (simvastatin & aspirin) for either 3 or 6 executive days. The control groups received the solvents only for the same periods. Biochemical markers of inflammation as serum tumor necrosis factor-α, interleukin-6 and interleukin-4 were measured by an Elisa method. Antioxidant activity was calorimetrically assessed by measuring serum nitric oxide concentration. Results indicated that treatment with simvastatin alone had no significant difference from treatment with aspirin alone which give solid ground for the predicted anti-inflammatory effects of simvastatin. Furthermore, our study demonstrated that treatment with the combined therapy reduced the extent of inflammation as compared to treatment with simvastatin alone or aspirin alone indicating that aspirin-simvastatin combination represents a synergistic combination concerning the immune response to the inflammatory challenge. The combination treatment with agents that inhibit different aspects of the signal transduction pathways will be transformational and have better efficacy with fewer side effects.